THE EFFECTS OF CHOLESTEROL DOSAGE, CORTISONE, AND DCA ON TOTAL SERUM CHOLESTEROL, LIPOPROTEINS, AND ATHEROSCLEROSIS IN THE RABBIT - Cook, Donald L. (The Rockefeller University Press, 1952)
The effects of cholesterol dosage, cortisone, and desoxycorticosterone acetate on total serum cholesterol, lipoproteins, and atherosclerosis were studied over a period of 112 days in thirty-two rabbits. Cholesterol was administered by feeding the rabbits diets containing 0.063, 0.25, and 1.0 per cent cholesterol At intervals measurements were made of total serum cholesterol and of low density lipid and lipoprotein components of three classes, S(f), 5–9, S(f) 10–15, and S(f) 16–30. All three classes of lipoproteins increased with cholesterol feeding. The total serum cholesterol concentration was linearly related to both the quantity of cholesterol consumed and its concentration in the diet. Lipoprotein and total serum cholesterol concentrations were significantly and equally well correlated with the severity of atherosclerosis. Cortisone administration in the normal rabbit increased the concentrations of total cholesterol and of lipoprotein components of the S(f) 10–15 and S(f) 16–30 classes, but did not produce atherosclerosis. Cortisone treatment in cholesterol-fed rabbits did not significantly affect the levels of serum lipoproteins, cholesterol concentration, or atherosclerosis produced by a 1.0 per cent cholesterol diet alone. Values for total cholesterol and S(f) 5–9 class of lipoproteins in DCA-treated animals were lower than those in controls but the degree of atherosclerosis was not significantly less.